Association between intrahepatic cholestasis of pregnancy and risk of gestational diabetes and preeclampsia: a systematic review and meta-analysis. (2nd July 2020) - Arafa, Ahmed; Dong, Jia-Yi
ABSTRACT: Objective: To investigate the association between intrahepatic cholestasis of pregnancy (ICP) and the risk of gestational diabetes mellitus (GDM) and preeclampsia via meta-analysis. Methods: Pooled odds ratio (OR) and confidence interval (CI) of GDM and preeclampsia for women with ICP were calculated using the fixed- or random-effects model. Results: Women with ICP were more likely to have GDM (pooled OR = 2.19, 95% CI: 1.58, 3.03, I 2  = 88.25%) and preeclampsia (pooled OR = 2.58, 95% CI: 2.37, 2.81, I 2  = 0%) than women without ICP. Conclusion: The present study supports the concept that ICP is associated with the risk of GDM and preeclampsia.